2019
DOI: 10.1186/s13104-019-4353-6
|View full text |Cite
|
Sign up to set email alerts
|

Gender differences in response to abdominal compartment syndrome in rats

Abstract: Objective Our study aims to emphasize the novelty of female rats in regard to their hemodynamic changes in response to abdominal compartment syndrome. A group of 64 rats was randomly divided into 4 subgroups for each gender. Except for the control, intra-abdominal pressure was increased to 10, 20, 30 mmHg. Survival time, mean arterial pressure, pH and lactate were determined at different time intervals. Results As IAP was 20 mmHg, a statistically difference was seen bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…38 As a limitation of the study, we only investigated male mice, even though some gender differences after blunt AT are likely and have been reported in rats during the development of an abdominal compartment syndrome. 39 Future studies need to also address the organ response in female mice.…”
Section: Discussionmentioning
confidence: 99%
“…38 As a limitation of the study, we only investigated male mice, even though some gender differences after blunt AT are likely and have been reported in rats during the development of an abdominal compartment syndrome. 39 Future studies need to also address the organ response in female mice.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, in the study by Barkai et al (2019), female rats showed greater resistance than male rats, as females demonstrated better preservation of their hemodynamic and metabolic parameters during abdominal compartment syndrome than males did.…”
Section: Discussionmentioning
confidence: 63%
“…Reintam-Blaser et al reported a borderline significant association between male sex and IAH among critically ill patients 35 . Additionally, it has been recently described that female rats develop better hemodynamic response after exposure to increased IAP and higher survival than their male counterparts, suggesting a possible role of sex hormones in the hemodynamic adaptation to IAH 38 . Patients that received peritoneal dialysis as renal replacement therapy suffered IAH less commonly when compared to hemodialysis subjects, a finding that has also been described in another transplant cohort 27 .…”
Section: Discussionmentioning
confidence: 99%